Covid-19 crisis management in Mýrdalshreppur and the significance of the government’s support measures for the municipality - Hannesdóttir, Hugrún; Bernharðsdóttir, Ásthildur Elva (Stofnun stjórnmála og stjórnsýslu, 2023)
This case-study focuses on how the South-Iceland rural community of Mýrdalshreppur responded to the Covid-19 pandemic. The community was among the worst hit municipalities economically. In addition to the analysis of the Mýrdalshreppur’s response the influences of the national government’s support for the local economy are highlighted. Crisis management forms the theoretical foundation as well as the research’s analytical framework. Research questions are examined through qualitative case-study. Fourteen first responders and locals were interviewed to collect data to find answers to the research questions. Main findings reveal that the government’s support-operations had significant effect, both those provided at the national-level, and the targeted support granted to Mýrdalshreppur. Covid-19 created multiple challenges for local businesses. The municipality council decided, early in the process to invest in construction, which turned out to be beneficial. Visible and apparent investments, along with targeted support made a positive impact which was perceived as recognition of the challenging situation felt by the local community. Local sense of solidarity was significant, but changes in demographics that have been evolving since 2010 will create long-term challenges. Þessi tilviksrannsókn beinir sjónum að hvernig fámennt sveitarfélag á landsbyggðinni, Mýrdalshreppur, tókst á við hið erfiða samfélagslega áfall sem fólst í Covid-19 faraldrinum en sveitarfélagið var eitt þeirra sem urðu fyrir hvað mestum efnahagslegum samdrætti vegna faraldursins. Auk greiningar á aðgerðum sveitarstjórnar voru dregin fram áhrif stuðningsaðgerða stjórnvalda til atvinnulífs sveitarfélagsins. Áfallastjórnun mótar hinn fræðilega grunn sem og greiningarramma rannsóknar og var leitað svara við rannsóknarspurningum með viðtölum við 14 viðbragðsaðila og heimamenn í Mýrdalshreppi. Meginniðurstöður sýndu að stuðningur stjórnvalda hefði haft mikla þýðingu, bæði aðgerðir á landsvísu og sértæki stuðningurinn sem Mýrdalshreppi var veittur. ...